SPASTICITY—Its Nature and Treatment - Levine, Milton G. (1954)
There are a number of physiological means of relaxing spasticity, including active resistive exercise, cold hydrotherapy, heat, electrical stimulation of antagonistic muscles, passive stretch in diagonal movement patterns, and the Von Bechterew reflex. Although none of them will cure spasticity, temporary relaxation may permit a patient to achieve better functioning of an affected joint. The choice of procedure will depend on the nature of the lesion and the muscular distribution of the spasticity.